2021
DOI: 10.1039/d1ra04882a
|View full text |Cite
|
Sign up to set email alerts
|

Semi-synthetic puwainaphycin/minutissamide cyclic lipopeptides with improved antifungal activity and limited cytotoxicity

Abstract: Both the substitution of free hydroxyl substituents and extending/branching of the fatty acid moiety improved the antifungal potency and limits the cytotoxicity of cyanobacterial cyclic lipopeptides puwainaphycin/minutissamides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The anti-proliferative activity of PUW F, MIN A-D, and MIN E-L has been reported in the literature, with different experimental settings and on different human cell lines (HeLa, colon carcinoma HT-29, and melanoma cell MDA-MB 435, respectively). , Recently, the cytotoxic activity of PUW/MIN variants with respect to the length of the FA moiety was studied by our team, and it was concluded that in a certain FA length span (C 12 –C 14 ), the cytotoxicity increases with the FA length but reduces further with FA extension . We used identical setting of the experiment and performed the cytotoxicity assays on human HeLa cells.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…The anti-proliferative activity of PUW F, MIN A-D, and MIN E-L has been reported in the literature, with different experimental settings and on different human cell lines (HeLa, colon carcinoma HT-29, and melanoma cell MDA-MB 435, respectively). , Recently, the cytotoxic activity of PUW/MIN variants with respect to the length of the FA moiety was studied by our team, and it was concluded that in a certain FA length span (C 12 –C 14 ), the cytotoxicity increases with the FA length but reduces further with FA extension . We used identical setting of the experiment and performed the cytotoxicity assays on human HeLa cells.…”
Section: Resultsmentioning
confidence: 76%
“… 19 , 20 Recently, the cytotoxic activity of PUW/MIN variants with respect to the length of the FA moiety was studied by our team, and it was concluded that in a certain FA length span (C 12 –C 14 ), the cytotoxicity increases with the FA length but reduces further with FA extension. 26 We used identical setting of the experiment and performed the cytotoxicity assays on human HeLa cells. To obtain a broader picture, we included four PUW/MIN variants ( 14 – 17 ) previously isolated, differing in their amino acid positions 4–8 from the PUW/MIN variants isolated from N. harveyana strain UHCC-0300 ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, several unique clusters, which may contribute to the specific antifungal activity of each Bcsl strain, were also detected. These include a BGC, only detected in the UW85 and LSTW-24 genomes, having similarity (21%–42%) for the NRPs-PKs hybrid locillomycin, reported to antagonize R. solani and F. oxysporum ( Luo, 2015 ) and a BGC found in S-10 and UW85 genomes with similarity (50–60%) to a puwainaphycin lipopeptide, which was previously shown to possess antifungal activity against members of the Ascomycota phylum ( Mares et al, 2019 ; Hajek et al, 2021 ). Interestingly, in our research we did not observe inhibition of F. oxysporum which represent the Ascomycetes soilborne pathogen, but this predicted gene cluster similar to puwainaphycin need to be further explored for its role in the inhibition activity of these two strains against R. solani and P. aphanidermatum .…”
Section: Discussionmentioning
confidence: 99%